For certain executive action in the Penal Code - Kuzmanova, Nikoleta (Law Journal of New Bulgarian University, 2022)
Numerous changes in the Penal Code over the last 30 years, which have been made at different times and for different reasons, have led to significant casuistry in the linguistic description of the executive act. The replacement of legal terminology with words from the colloquial Bulgarian language created a normative paradox – describing one and the same prohibited behavior in one or different types of crimes through synonyms from the Bulgarian language. The adoption of legislative practice for the literal reproduction of terminology from international acts and acts of European Union’s law, which are subject to introduction into criminal law, has further aggravated this problem. Overcoming it is essential for the proper application of criminal law, as it has direct connection with the differentiation of the scope of the various forms of the act. In some cases it turns out impossible even though a significant volume of interpretive activity has been done. Moreover, the inconsistent use of the same descriptions of executive acts, in view of the differences in other constituent features, also leads to different meanings of the same term in the composition of different crimes. The present study focuses only on some of these cases, grouped by the basis of their common starting point for their criminal law content – “accept – receive – acquire”; “holds – stores – carry over – ships – transports” and “transports across the border – imports – exports”.